2022
DOI: 10.3390/agronomy12030744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparative Analysis of Meteorological Data, Moisture Content, and Rice Panicle Threshability

Abstract: Harvesting and threshing are crucial processes that influence the quantity, quality, and economic efficiency of rice production. Therefore, the threshability of rice varieties is an important agronomic trait for breeding programs. However, selection for threshability is hardly standardized. With the application of an improved threshing meter, the threshability of four local temperate japonica rice varieties was determined during the ripening phase (DAF 37–60) in three consecutive years. Panicle threshing force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…No significant differences were recognized among the varieties in aerobic conditions. In one case, however, we found a significant difference between two tested varieties ('M 488' and 'Nembo') in flooded conditions on soil treated with Humin Power G soil conditioner (SZALÓKI et al, 2022).…”
Section: Genetical Variation In As Accumulationmentioning
confidence: 60%
See 1 more Smart Citation
“…No significant differences were recognized among the varieties in aerobic conditions. In one case, however, we found a significant difference between two tested varieties ('M 488' and 'Nembo') in flooded conditions on soil treated with Humin Power G soil conditioner (SZALÓKI et al, 2022).…”
Section: Genetical Variation In As Accumulationmentioning
confidence: 60%
“…In our previous greenhouse pot experiment, the As concentration of the above-ground biomass was significantly higher in flooded than in aerobic conditions, as Figure 1. shows (SZALÓKI et al, 2022).…”
Section: Water Managementmentioning
confidence: 97%
“…In our previous study, we examined the As content of shoots of four rice varieties in different irrigation systems (flooded and aerobic). No significant differences were found among the varieties in aerobic conditions [33].…”
Section: Introductionmentioning
confidence: 73%
“…We found that the As concentration of the straw was significantly higher with flooded irrigation than with aerobic irrigation. However, due to the relatively low As concentration in the soil (10.6 mg kg −1 ), no phytotoxic effects on the plants were observed [33]. Several researchers have also reported that aerobic water management practices significantly decreased the total As concentration of rice straw as well as grain compared to anaerobic systems [32,[49][50][51].…”
Section: Water Management Practices and As Uptakementioning
confidence: 99%
“…In the first article, Szalóki et al [21] determined the threshability of four local temperate japonica rice varieties during the ripening phase over three consecutive years with the application of an improved threshing meter. In this context, harvesting and threshing are crucial processes that influence the quality, quantity, and economic efficiency of rice production.…”
Section: Evolution Of Compounds and Characteristics Of Crops During R...mentioning
confidence: 99%